Osteogenic induction of human Wharton’s jelly‐derived mesenchymal stem cells using a composite scaffold from poly(ɛ‐caprolactone) and biosilica sponge Xestospongia testudinaria - Andika Ardiyansyah; Anggraini Barlian; Candrani Khoirinaya; Sony Heru Sumarsono (Universitas Gadjah Mada, 2025)
Bone defects occur when bones cannot function properly due to trauma, such as accidents. In Indonesia, such defects are mainly treated by bone grafting, but the limited availability of transplants has led to the development of bone tissue engineering as an alternative. This study uses human Wharton’s jelly‐derived mesenchymal stem cells (hWJ‐MSCs) as these can differentiate into osteoblasts when stimulated by a composite scaffold containing biosilica from the sponge Xestospongia testudinaria. Four main steps were performed in this study, i.e. scaffold fabrication with varying biosilica concentrations, material characterization to see whether the scaffold resembled bone tissue, hWJ‐MSC isolation from the umbilical cord and cultured until passage 6, and scaffold testing to assess its compatibility and ability to support cell adhesion, proliferation, differentiation, and mineralization into bone cells. The results indicated that a scaffold with 50% biosilica has good properties for supporting hWJ‐MSC growth, proliferation, and differentiation. The scaffold exhibits strong mechanical strength and hydrophilic characteristics, enhances cell proliferation, and promotes osteogenic differentiation, as confirmed by collagen type I and osteopontin expression with a higher optical density value in the Alizarin Red assay. Therefore, the 50% biosilica composite scaffold is biocompatible and osteoconductive, making it a promising candidate for bone tissue engineering.